Ignorance is bliss: Rationality, information and equilibrium - Sylvain Barde (University of Kent, School of Economics, 2011)
An information-theoretic thought experiment is developed to provide a methodology for predicting endowment distributions in the absence of information on agent preferences. The allocation problem is first presented as a stylised knapsack problem. Although this knapsack allocation is intractable, the social planner can nevertheless make precise predictions concerning the endowment distribution by using its information-theoretic structure. By construction these predictions do not rest on the rationality of agents. It is also shown, however, that the knapsack problem is equivalent to a congestion game under weak assumptions, which means that the planner can nevertheless evaluate the optimality of the unobserved allocation.
Keywords: C02; C62; D51; D83; 330; Information theoretic measure; knapsack problem; congestion game; potential function